Acquisition of Productive Vocabulary in Higher Academic Contexts: Analysis of its evolution from a Longitudinal Study - Gonzalo Zapico, Martín (2018)
Vocabulary, both in its productive and receptive dimension, is a fundamental element when facing an academic major. In this context, its measurement and the possibility of understanding how it is acquired becomes fundamental in order to design concrete intervention policies that help to palliate dropouts, particularly the first year of many higher education majors. In this framework, the results of an analysis carried out through the four-year follow-up of a group of students who were applied a test of productive vocabulary four times, one at the beginning of each school year are shown. The results suggest that the acquisition of vocabulary is based on the rearrangement of concepts, similar to an exponential function.